2021
DOI: 10.1177/19476035211046040
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Molecular Evaluation of the Tissue Repair following Nasal Septum Biopsy in a Sheep Model

Abstract: Objective Nasal septal pathologies requiring surgical intervention are common in the population. Additionally, nasal chondrocytes are becoming an important cell source in cartilage tissue engineering strategies for the repair of articular cartilage lesions. These procedures damage the nasal septal cartilage whose healing potential is limited due to its avascular, aneural, and alymphatic nature. Despite the high incidence of various surgical interventions that affect septum cartilage, limited nasal cartilage re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Human activities are inseparable from joint movement, and articular cartilage plays a role in relieving stress and lubricating joints. Once the cartilage is damaged or degenerated [ 1 , 2 ], it is difficult to repair itself, because the main components of articular cartilage are collagen fibers and proteoglycans in addition to water, which lack a blood supply and cells cannot migrate to the defect site [ 3 ]. At present, the surgical treatment of cartilage defects mainly involves the direct use of growth factors, autologous transplantation, or allogeneic transplantation [ 4 ], but there are several problems, such as limited donor sites and immune responses [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Human activities are inseparable from joint movement, and articular cartilage plays a role in relieving stress and lubricating joints. Once the cartilage is damaged or degenerated [ 1 , 2 ], it is difficult to repair itself, because the main components of articular cartilage are collagen fibers and proteoglycans in addition to water, which lack a blood supply and cells cannot migrate to the defect site [ 3 ]. At present, the surgical treatment of cartilage defects mainly involves the direct use of growth factors, autologous transplantation, or allogeneic transplantation [ 4 ], but there are several problems, such as limited donor sites and immune responses [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Articular cartilage defects are common and often lead to gradual tissue degradation, joint pain, dysfunction and degenerative arthritis [1,2]. However, as articular cartilage is avascular and aneural tissue with poor inherent repair ability, its regeneration is one of the most challenging clinical problems surgeons and scientists face [3,4]. Cell-based tissue engineering techniques that promote cartilage self-repair with stem cell manipulation techniques, biological scaffolds, and biological factors have been extensively studied to address this challenge [5].…”
Section: Introductionmentioning
confidence: 99%
“… 11 Several studies have demonstrated that nasal cartilage can serve as a source to replace lost hyaline cartilage in joints. 2 - 6 There is an unmet clinical need to be able to engineer hyaline cartilage that is functionally stable and able to respond to local requirements, such as mechanical compression, lubrication, ability to withstand inflammatory signals. A comprehensive literature review addressing those topics in relation to tissue engineering of the nasal cartilage was recently published 11 and thus they will not be further considered here.…”
Section: Introductionmentioning
confidence: 99%
“…1 The thickest part of the NSC is the area connected to the vomer and PPE, which has clinical implications during reconstructive surgery and tissue engineering. [1][2][3][4][5][6] NSC is avascular, devoid of neural and lymphatic supply, and is surrounded by perichondrium and respiratory epithelium. According to its location, it articulates with the frontal bone, nasal bone, cribriform plate, sphenoid bone, maxillary crest, vomer, and palatine bone.…”
Section: Introductionmentioning
confidence: 99%